Equilibrium traffic assignment on large Virtual Networks: Implementation issues and limits for multi-modal freight transport - Jourquin, Bart; Limbourg, Sabine (European Journal of Transport and Infrastructure Research, 2006)
Multi-Modal freight models are traditionally built following the well known “four steps model” in which generation, distribution, modal-split and assignment are seen as separated modules. An alternative approach, now implemented in some software, is to represent the multi-modal network by means of a “mono-modal” one, in which each particular transport operation (loading or unloading operation, transhipments ...) is represented by a dedicated “virtual link”, that represents a specific operation in the transportation chain. This approach, promoted by several authors, often referenced to as “super networks” or “virtual networks”, is proven to give interesting results, but has the drawback to generate much larger networks than the pure geographic representation of the studied area. It has also some kind of “hidden trap”, linked to transport distances, that will be presented in this paper and that can only be solved using appropriate assignment techniques. This paper presents some results obtained on a large multi-modal network, using different equilibrium assignment algorithms, in order to test their ability to give an appropriate solution to the “distance trap”. It however concludes that the implementation of classical equilibrium assignment techniques leads to solutions that are barely different from the one obtained by a simple all-or-nothing assignment, opening the way to alternative multi-flow solutions.